Evidence Based Nutrition and the Integrated Librarian - Amanda Rose Horsman (Journal of the Canadian Health Libraries Association, 2015)
Program objective: Integration of a medical librarian into undergraduate nutrition Professional Practice class with an evidence based nutrition component. The objective of this integration is to increase the success rate of the PEN (Practice Evidence Nutrition) project.